2022
DOI: 10.1117/1.jrs.16.026505
|View full text |Cite
|
Sign up to set email alerts
|

Optimal band selection for target detection with a LWIR multispectral imager

Abstract: Multispectral imaging can offer many benefits in cost, complexity, resolution, size, weight, and power, relative to hyperspectral imaging. When designing a multispectral system, spectral bandpasses can be selected using optimization algorithms configured to maximally separate target detection scores between target and background regions. A hyperspectral image (HSI) can serve as the source of data from which band groupings can be tested for optimality. The output of an adaptive cosine estimator target detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…These authors implemented both SVMs and random forests as classifiers and showed results for the Pavia University dataset and the Indian Pines dataset. Also in 2022, a rather comprehensive study was published by Zelinski et al 25 from Lawrence Livermore National Lab. These authors compared the band-selection results from three different integer-programming algorithms against those from a brute-force search performed on a supercomputer.…”
Section: Previous Workmentioning
confidence: 99%
“…These authors implemented both SVMs and random forests as classifiers and showed results for the Pavia University dataset and the Indian Pines dataset. Also in 2022, a rather comprehensive study was published by Zelinski et al 25 from Lawrence Livermore National Lab. These authors compared the band-selection results from three different integer-programming algorithms against those from a brute-force search performed on a supercomputer.…”
Section: Previous Workmentioning
confidence: 99%
“…Multispectral uncooled infrared (IR) sensors are attracting interest for use in applications such as gas analysis, hazardous material recognition, biological analysis, and multi-wavelength imaging. [1][2][3] However, conventional sensors require additional filters or a resonant structure in the vertical direction, [4][5][6] which causes high cost and requires complicated integration procedures. To address this challenge, plasmonic metamaterial absorbers (PMAs) such as plasmonic crystals (PCs), [7][8][9] metal-insulator-metal (MIM), [10][11][12] and mushroom-type PMAs [13][14][15][16] are being widely investigated as IR absorbers.…”
Section: Introductionmentioning
confidence: 99%